Assessment of the awareness, adherence, and barriers to low back pain clinical practice guidelines by practicing physiotherapists in a low‐resourced country. (21st October 2019) - Akindele, Mukadas; Rabiu, Mubasshir; Useh, Efe
Abstract: Background and Objectives: Many clinical practice guidelines (CPGs) for low back pain (LBP) management have been developed, but adherence to CPGs seems to be challenging as developing them in the first place. This cross‐sectional survey study was carried out to determine the awareness level, the level of adherence, and barriers to adherence to CPGs of LBP among physiotherapists in Nigeria. Methods: A total of 189 participants were recruited for this study using the convenience sampling technique. The data were collected using researcher‐designed questionnaires, the data were analysed using SPSS Version 20, and barriers to adherence to CPGs of LBP was analysed using simple thematic analysis. Descriptive statistics, frequency, and percentage were used to summarize the data, whereas inferential statistic of chi square and Fisher's exact were used to test the association between sociodemographic variables and adherence. Results: The results obtained showed that only a small percentage (27.50%) of the respondents adhered to LBP CPGs, whereas higher percentage (78.80%) was aware to the LBP CPGs. There were no significant associations between age ( p = .90, χ 2 = 0.72), certification courses ( p = .476, χ 2 = 0.508), place of practice ( p = .380, χ 2 = 0.845), and adherence to CPGs of LBP, respectively. However, there was a statistical significant association between specialization ( p = .009, χ 2 = 16.725), political zone ( p = .007, χ 2 = 15.243), awareness ( p = .003, χ 2 = 8.957), and adherence to CPGs of LBP, respectively. Conclusion: Small proportions of the respondents adhered to the LBP CPGs, whereas higher population were aware of the LBP CPGs, and some of the characteristics of the physiotherapists influence adherence to LBP CPGs.